Methodologies to assess the development impact of loan aid: the European experience - BUENDÍA, Luis (Revista Iberoamericana de Estudios de Desarrollo)
In this paper we analyse the methodologies used by the main European Development Finance Institutions (EDFIs) to assess the development impact of their operations. To do so, we identify the selection criteria of the projects funded by EDFIs using both a literature review —including their own web pages— and on-site interviews. The article concludes that the methodologies used by these institutions have important shortcomings to the extent that there is no an analysis of the institutional framework in which these operations take place. Therefore, the development impact attributed thereto is debatable.